History-Based Tourism Development: A Case Study of the Tourism Office's Strategy in Increasing the Attractiveness of Fort Kuto Besak Palembang - Nova Rahma Kurnia; Isabella; Doris Febriyanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Historical tourism plays a crucial role in supporting economic development, cultural preservation, and enhancing regional image. As one of Indonesia's oldest cities, Palembang boasts a rich historical heritage with potential for development, one example being Kuto Besak Fortress. This fort not only reflects the glory of the Palembang Darussalam Sultanate but also holds a strategic position as a city tourism icon. This study aims to determine the strategy of the tourism office in increasing the historical tourist attraction of Kuto Besak Fortress in Palembang City. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation and documentation at the Palembang City Tourism Office and Kuto Besak Fortress in Palembang City. Data analysis was carried out through data collection, data presentation and verification and confirmation of conclusions. At the research location was conducted at Jl. Dr. Wahidin No. 3, Talang Semut. Bukit Kecil District, Palembang City, South Sumatra 30121. And Jalan Sultan Mahmud Badarudin, 19 Ilir, Bukit Kecil District, Palembang City By conducting observation, interview and documentation stages and conducting research objectively. Interview sources numbered 11 informants including 1 head of the office, 3 tourism office employees, and 7 members of the public. The results of this study found a strategy implemented by the Palembang City Tourism Office that includes quite comprehensive planning aspects, such as increasing tourism promotion through digital media through websites and social media, organizing annual events, and involving the community and local stakeholders in the development of historical tourism, making it a potential tourist attraction. However, in implementing this strategy, several major obstacles were identified, including the Tourism Office facing challenges such as limited budget and human resources, coupled with low public awareness of cleanliness and security, the presence of illegal buskers, thuggery, unorganized street vendors, and illegal parking still disrupting the comfort and image of tourists visiting Kuto Besak Fortress. Collaboration between the government and the community is the main key to making Kuto Besak Fortress a historical tourist destination that is not only attractive, but also comfortable, safe, and sustainable for all groups. In conclusion, this study concludes that the Palembang City Tourism Office has made significant efforts to develop Kuto Besak Fort as a historical tourism destination. Through a combination of planned and adaptive strategies, despite facing several obstacles, it is hoped that Kuto Besak Fort will continue to grow into a leading tourist attraction that contributes to the preservation of history and the local economy of Palembang City.